Breeding policies and management of pedigree dogs in 15 national kennel clubs. (April 2018) - Wang, S.; Laloë, D.; Missant, F.M.; Malm, S.; Lewis, T.; Verrier, E.; Strandberg, E.; Bonnett, B.N.; Leroy, G.
Highlights: Respondents to the survey were national kennel clubs (KCs) from 11 European and four non-European countries. KCs report progress in the collection and provision of health information. Exaggerated morphologies and inherited disorders are viewed as the most important issues. A wide diversity of breeding tools and strategies exist across breeds and countries. Getting a consensus on breeding priorities remains an important challenge. Abstract: To improve the health and welfare of pedigree dogs, national kennel clubs (KCs) are key players in the governance and regulation of dog breeding. In a survey conducted to investigate differences between KCs in breeding policies and management of pedigree dogs, a questionnaire was completed by 15 KCs from 11 European countries (Austria, Belgium, Denmark, France, Germany, Ireland, Latvia, The Netherlands, Norway, Sweden and the United Kingdom) and four non-European countries (Australia, Mexico, Uruguay and the USA). The most important concerns reported by KCs were exaggerated morphological features and inherited disorders. A wide variety of information, tools and strategies was used to address these issues, with implementation differing across countries and breeds. KCs reported progress in the collection and provision of information related to canine health and welfare. Implementation of advanced breeding tools, such as genetic evaluation and online advisory mating tools, and balanced breeding strategies, endorsed by clubs and breeders, remain challenging and require further development.